Matrix gla protein in xenopus laevis: molecular cloning, tissue distribution, and evolutionary considerations - Cancela, M. Leonor (2001)
Matrix Gla protein (MGP) belongs to the family of vitamin K-dependent, Gla-containing proteins and in higher vertebrates, is found in the extracellular matrix of mineralized tissues and soft tissues. MGP synthesis is highly regulated at the transcription and posttranscription levels and is now known to be involved in the regulation of extracellular matrix calcification and maintenance of cartilage and soft tissue integrity during growth and development. However, its mode of action at the molecular level remains unknown. Because there is a large degree of conservation between amino,acid sequences of shark and human MGP, the function of MGP probably has been conserved throughout evolution. Given the complexity of the mammalian system, the study of MGP in a lower vertebrate might be advantageous to relate the onset of MGP expression with specific events during development. Toward this goal, MGP was purified from Xenopus long bones and its N-terminal amino acid sequence was determined and used to clone the Xenopus MGP complementary DNA (cDNA) by a mixture of reverse-transcription (RT)- and 5'- rapid amplification of cDNA ends (RACE)-polymerase chain reaction (PCR). MGP messenger RNA (mRNA) was present in all tissues analyzed although predominantly expressed in Xenopus bone and heart and its presence was detected early in development at the onset of chondrocranium development and long before the appearance of the first calcified structures and metamorphosis. These results show that in this system, as in mammals, MGP may be required to delay or prevent mineralization of cartilage and soft tissues during the early stages of development and indicate that Xenopus is an adequate model organism to further study MGP function during growth and development.